Preparation of poly (vinylindene fluoride-co-hexafluoriproylene) composite membranes for treatment of water hardness - Ramollo, Khaleke Veronicah (My University, 2022)
Calcium and magnesium are two dominant species that contribute to water hardness. The aim of this study was to develop a poly (vinylidene fluoride-co hexafluoropropylene) (PVDF-HFP) composite membrane for treatment of water hardness. The synthesis of PVDF-HFP composite membranes was confirmed by X ray diffraction (XRD), scanning electron microscopy (SEM), thermogravimetric analysis (TGA) and Fourier transform infrared (FTIR) spectroscopy. The concentrations of the hardness causing agents in both the simulated and real hard water samples were investigated in batch studies wherein parameters such as pH, contact time, temperature, and adsorbent were optimised. The maximum adsorption efficiency of 56 and 45 mg/g (evaluated by Langmuir isotherm) for Ca(II) and Mg(II) ions were obtained. These were achieved at an optimum pH of 7 and adsorption dosage of 0.5 mg/L using the 3% PVDF-HFP/cellulose acetate (CA) and 1% nitrogen doped multiwalled carbon nanotubes (N-MWCNTs)/CA composite membranes respectively. The adsorption kinetics and isotherm models were all consistent with the pseudo-second order and Freundlich isotherm models for all the membranes suggesting that the sorption process met heterogeneous adsorption. Furthermore, the thermodynamic parameters indicated that the adsorption is physical and endothermic in nature. Reusability studies showed that all the PVDF-HFP based membranes can be recycled at least 3 times and for Ca(II) ions an adsorption loss of only 0.35 % was recorded while using a 3% PVDF-HFP/CA composite membrane. These results were further confirmed by XRD, TGA and inductively coupled plasma mass (ICP-MS) spectrometry. Thus, the findings from this study have shown that the PVDF-HFP based membranes could provide valuable material for hardness removal to acceptable level.
Thesis (M.Sc. (Chemistry)) -- University of Limpopo, 2022
Keywords: Vinylindene fluoride-co-hexafluoriproylene; Poly composite membranes; Water hardness; Water -- Hardness; Water -- Purification; Fourier transform infrared spectroscopy; Water treatment plants